Electronic Health Book System by Using Android Based Application - Rijet, Valerie Vilyn; Wan Kairuddin, Wan Nur Hafsha (Evolution in Electrical and Electronic Engineering, 2023)
The traditional techniques of providing services by health professionals are being reshaped by e-Health, to reduce costs and increase patient-users with health services. The increased number of patients registering per year causes data health collection more difficult and easier to misplace as paper-based data collection is still being used. The purpose of this project is to design E-Health Book which is an Android-based application that to is used by patients and hospital staff. The proposed system is developed using Flutter, a software development kit (SDK) for cross-platform app development, and uses DART as a programming language. The outcome of this project is an Android-based application whose efficiency was evaluated by respondents from a specific background that will benefit from the application using a set of questions that was prepared by using the Technological Acceptance Model (TAM) to construct the questionnaire to assess the efficiency of the application. The application received overwhelmingly positive feedback, where 100% of the respondents that participated in the survey expressed complete satisfaction and inclination to highly recommend it to their acquaintances.